Digital Marketing and Consumer Engagement: A Systematic Review - Abdul Haris (Amkop Management Accounting Review (AMAR), 2023)
This comprehensive literature review explores the multifaceted landscape of digital marketing and consumer engagement. The study examines the evolution of digital marketing strategies, consumer behavior in the digital age, and the challenges and ethical considerations inherent in digital marketing practices. Employing a systematic approach, the research design thoroughly examines scholarly sources to elucidate critical themes and findings. Findings indicate that digital marketing has evolved significantly, offering businesses unparalleled opportunities to engage with consumers across diverse platforms. Search engine optimization (SEO), content marketing, social media marketing, and influencer marketing have become potent tools for enhancing brand visibility and fostering consumer interaction. However, the study also highlights challenges such as algorithmic bias and ethical considerations, emphasizing the importance of transparency and accountability in digital marketing practices. The discussion underscores the critical role of consumer engagement and moral principles in shaping the future landscape of digital marketing. Implications suggest that businesses prioritize ethical best practices and adopt an integrated approach to digital marketing to drive sustainable growth and cultivate enduring relationships with consumers, navigating the evolving digital landscape effectively.